2015
DOI: 10.1680/stbu.12.00078
|View full text |Cite
|
Sign up to set email alerts
|

Crack detection in concrete gravity dams using a genetic algorithm

Abstract: The main aim of this paper is to introduce an efficient procedure for crack detection in concrete gravity dams. A genetic algorithm and finite-element modelling are employed to perform the optimisation tasks. A two-dimensional cracked element is formulated for non-linear analysis. In this investigation, the kinematics of the discontinuous displacement field in a body with an internal discontinuity is utilised. Based on the suggested interpolation functions for the discrete segments, and also the element displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Rezaiee-Pajand and Tavakoli [11] introduced an efficient method for crack detection in concrete gravity dams using a hybrid genetic algorithm (GA) and FE methods. The GA identifies the location and magnitude of cracks in dams by minimizing the difference between the analytical responses and the measured ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rezaiee-Pajand and Tavakoli [11] introduced an efficient method for crack detection in concrete gravity dams using a hybrid genetic algorithm (GA) and FE methods. The GA identifies the location and magnitude of cracks in dams by minimizing the difference between the analytical responses and the measured ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cracks seriously damage the reliability and longevity of the structure; they can exist not only at the structure's surface but can also extend into the interior [7,8]. Zhang and Zhuang [9,10] proposed a self-propagating strong discontinuity embedded approach with the statically optimal symmetric (SDA-SOS) formulation to study the propagation law of cracks. Their computational examples showed that cracks seriously degrade structure durability.…”
Section: Introductionmentioning
confidence: 99%
“…Out of these, cracks represent the primary danger because they can exist not only at the dam’s surface but also extend into the interior [ 2 ]. In other words, cracks in dams are the equivalent of mutations as dams accumulate internal damage [ 3 ]. Thus, cracks are always used to indicate the degree of risk in the field of dam damage, which has attracted the attention of numerous scholars [ 4 ].…”
Section: Introductionmentioning
confidence: 99%